The surplus labor force in Argentina: An analysis from feminist economics - Alonso, Virginia Noemí (2024)
This article takes up the concept of surplus labor force as understood in Latin American economic thought, due to its importance in pointing out the difficulties of capitalism in incorporating people into quality jobs and explaining the reproduction of inequalities. To contribute to the study of women’s labor exclusion in the region, two objectives are pursued. The first objective is to construct a theoretical-methodological proposal to study the surplus of the labor force by re-reading the structuralist approach from a feminist economics perspective. The second objective is to analyze with this adapted framework the evolution of the surplus of the labor force, as well as the Argentine welfare policy that aims to regulate it and its link with the reproduction of gender inequalities at the national level between 2003 and 2019. For this purpose, a documentary and statistical analysis of different sources is carried out. The results show the structural persistence of exclusion and gender inequality as a result of the articulation between the labor features of the Argentine development style and the consolidated welfare policy pattern. This pattern is based on conditional cash transfers and was functional to the feminization of the surplus of the labor force during the first two decades of the 21st century.